Development of a Nanoscale-Sensitive DNA Sensor using Functionalized Graphene Substrates and Fluorescence Lifetime Characterization - Adão, Ricardo Miguel Ribeiro (2017)
Fluorescence Lifetime Image Microscopy (FLIM) of nanostructured graphene substrates was used to measure the recently observed nanoscale distance-scaling of the fluorescence lifetime of dyes located in the vicinity of graphene sheets, at distances up to about 30 nm. The results were compared with a Resonant Energy Transfer (RET) theoretical model and used to establish an experimental fluorescence lifetime-to-nanoscale distance conversion function. In the following, this nano-optical relation was used for the design of a Deoxyribonucleic Acid (DNA) biosensor. Graphene was functionalized with fluorescently labeled DNA molecular beacons that unfold during hybridization with complementary DNA, and thereby change the distance of the fluorescent dye from the graphene surface. The spatial distribution of DNA molecular beacons binding to the surface of a graphene flake was studied, as well as the temporal kinetics of the hybridization reaction using time-lapse FLIM measurements. The results showed a vertical ascent of a fluorescent label relative to the graphene surface with a distance extension that is in accordance with the expected molecular length of the specific DNA sequence used. Interestingly, an intermediate state associated to a distance of a few nanometers was identified with a lifespan of about 85 minutes. The developed graphene-based DNA sensor was shown to enable optical detection of nanoscale distances in liquid media. These findings indicate that the fluorescence lifetime-based detection coupled with nanoscale interaction effects may find applications in various biosensing applications such as health and food-quality tracing. For the processing of FLIM data, several fluorescence lifetime calculation algorithms were compared and integrated into a specially designed and implemented analysis software toolbox in MATLAB.